Synthesis of Boron Carbide Powder via Rapid Carbothermal Reduction Using Boric Acid and Carbonizing Binder - Bing Feng; Hans-Peter Martin; Alexander Michaelis (Ceramics, 2022)
Raw material is one of the most decisive factors for the quality of sintered boron carbide (B4C) products, in the past, there were relatively successful efforts for the synthesis of B4C powders via carbothermal reduction approaches. To prepare high-quality powder, a deeper understanding of the relationship between technological manufacturing parameters and resulting powder properties is required. In this paper, pure B4C powders were synthesized by rapid carbothermal reduction (RCR) under B2O3 excess conditions using boric acid and a carbonizing binder as B2O3 and carbon source, respectively. The molar ratio of B2O3/C of starting mixtures was varied from 0.75:1 to 4:1. The effects of heat-treating temperature and starting composition on phase constitution, morphology as well as stoichiometry of the prepared powders were investigated. The studies show that the starting composition has no effect on the stoichiometry of the powders, all boron carbides synthesized at 1900 °C have a stoichiometric composition of B4C. With increasing heating temperature and B2O3 content in the starting composition, the particle size of B4C was reduced. Uniform B4C powders with an average grain size of 300 nm were synthesized at 1900 °C from a starting powder mixture with a molar ratio of B2O3/C = 4. A formation mechanism is proposed under large B2O3 excess conditions. For the starting powder mixtures with a molar ratio of B2O3/C < 2, the formation of boron carbide occurs through both liquid–solid reaction and gas–solid reaction. Accordingly, the synthesized powders exhibit a morphology with mixed elongated platelets and small polyhedral particles. For the starting powder mixtures with a molar ratio of B2O3/C ≥ 2, fine-sized B4C particles were formed by a liquid–solid reaction.